Turkish Foreign Policy in the XXIst Century: Peace in the World, Not in the Home - McLean, Jessica Y. (Université d'Ottawa | University of Ottawa, 2012)
This research paper examines the evolution, successes, failings and future challenges of Turkey’s current foreign policy and its impact on regional power dynamics. From failed Empire to modern Republic to regional power, Turkish diplomacy has experienced a notable shift in purpose, branding and execution, reflecting its own domestic socio-economic progress and adapting to ever changing world events and crises. Through what the ruling Justice and Development Party coins as “Strategic Depth”, the current government is seeking to maximize Turkey’s shared history, culture, language and religion to strengthen strategic cooperation, broker profitable economic agreements and reduce its problems with neighbours down to zero. By balancing multiple strategic alliances to the East and to the West, Turkey’s newly invigorated diplomacy has succeeded in moving the country from the periphery of international relations to the centre. Among the notable diplomatic successes are the heightened profile of Turkish humanitarian assistance in places like Somalia and Afghanistan, the fruitful conflict mediation in the Balkans and the ongoing diplomatic viability vis-à-vis Iran’s nuclear program. While Turkish soft power foreign policy has been successful in fostering peace for others, it has been unsuccessful in achieving peace for itself. A host of national and international obstacles challenge the sustainability of the government’s foreign policies while festering stalemates with neighbouring countries wear away at the credibility of Turkish regional leadership.